Sosialisasi Konsep Smart Village Berdasarkan SDGs - Eliyah A M Sampetoding; Muhammad Sadno; A. Muh. Amil Siddik; Edy Saputra Rusdi; Hendra Mesra; Jeriko Gormantara (Compromise Journal Community Proffesional Service Journal, 2024)
Digital transformation plays an important role in improving people's welfare, especially in rural areas. The first step in realizing the concept of a Digital Village, Smart Village, and achieving the Sustainable Development Goals (SDGs) involves the integration of information and communication technology to improve efficiency, accessibility and public services. Digital Villages experience change through the implementation of digital basic infrastructure and increased technological literacy, while Smart Villages optimize the use of data and technology-based solutions to improve village governance. Achieving the SDGs is the main goal in designing sustainable solutions. Hasanuddin University's Information Systems Study Program supports efforts to achieve SDGs in assisted villages, including Peace Villages in Maros Regency. The initial socialization regarding Smart Village has attracted the interest of residents, and the potential for implementation by the Academic Community from Study Programs in the Village has also received support.